Moderate coffee consumption reduces the risk of hepatocellular carcinoma in hepatitis B chronic carriers: a case–control study. Issue 6 (6th August 2010) - Leung, Winnie Wing-man; Ho, Suzanne C; Chan, Henry L Y; Wong, Vincent; Yeo, Winnie; Mok, Tony S K
Abstract : Background: Recent epidemiological studies have reported a dose-dependent protective effect of coffee on hepatocellular carcinoma (HCC) with risk reduction ranging from 30% to 80% in daily coffee drinkers compared with non-drinkers. This study examined whether coffee has a similar protective effect when consumed in moderate quantities in chronic hepatitis B virus (HBV) carriers, a group at high risk of developing liver cancer. Methods: A case–control design was employed. 234 HBV chronic carriers (109 cases and 125 controls) were recruited from the Prince of Wales Hospital in Hong Kong from December 2007 to May 2008. Data collection included review of medical records and face-to-face interview. Univariate and multivariate logistic regressions adjusting for age, gender, cigarette smoking, alcohol use, tea consumption and physical activity were conducted with dose–response analysis. Results: Moderate coffee consumption significantly reduced the risk of HCC by almost half (OR 0.54, 95% CI 0.30 to 0.97) with a significant dose–response effect (χ 2 =5.41, df=1, p=0.02), reducing the risk for moderate drinkers by 59% (OR 0.41, 95% CI 0.19 to 0.89). Conclusion: The findings provided evidence to support the protective effect of coffee consumption in moderate quantities in HBV chronic carriers.